MAPPING RESEARCH TRENDS ON ENTREPRENEURIAL READINESS IN VOCATIONAL EDUCATION: IMPLICATIONS FOR INDONESIA (2020–2025) - Shilmi Arifah; Ansheila Rusyda Subiyantari; Tuti Iriani; Sudirman Rizki Ariyanto (Universitas Labuhanbatu, 2026)
Purpose – This study systematically maps global research trends on entrepreneurial readiness in vocational education from 2020 to 2025 and identifies implications for strengthening the Indonesian vocational education system (SMK). Entrepreneurial readiness is a strategic national priority amid ongoing graduate unemployment and policy reforms, including Merdeka Belajar.Methodology – A bibliometric analysis was conducted using data from the Scopus database. After a multi-stage screening, 82 relevant publications were selected from an initial pool of 159 documents. Subsequently, the VOSviewer software generated keyword co-occurrence networks and temporal overlay visualizations, enabling the identification of thematic clusters and the evolution of research focus.Findings – The analysis identified 29 key terms within five thematic clusters: (1) Entrepreneurial Readiness, (2) Work-Integrated Learning, (3) Entrepreneurial Self-Efficacy, (4) Entrepreneurial Intention, and (5) Entrepreneurial Education. Early studies (2020–2021) centered on employability skills, curriculum design, and work-integrated learning, while recent research (2022–2025) focused on digital competence, self-efficacy, leadership, and innovation. These thematic trends correspond to Indonesia's digital economic growth and national reforms in vocational education under the Merdeka Belajar framework. However, notable gaps persist in bibliometric studies tailored to the Indonesian vocational education context, specifically highlighting the need for targeted research.Contribution – This study maps the field of entrepreneurial readiness research in Indonesian vocational education, strengthens the integration of the Theory of Planned Behavior with work-integrated learning and digital competence, and offers actionable policy insights for redesigning SMK curricula under the Merdeka Belajar framework.